Hitting the bullseye: Learning to become a reflexive monitor in New Zealand. (June 2017) - Fielke, Simon; Nelson, Tracy; Blackett, Paula; Bewsell, Denise; Bayne, Karen; Park, Nicola; Rijswijk, Kelly; Small, Bruce
Reflexive monitors (RMs) have been found to be vital to the success of co-innovation projects. While the practices utilized by RMs have been examined in various contexts, we examine the roles they have played in a new cultural context in New Zealand (NZ) and how it has been possible to embed these roles in a diverse range of innovation projects in the primary sector. This article will address this gap in terms of explaining the case-specific behaviours that have been utilized in six different co-innovation projects in the NZ agricultural innovation system. Qualitative data from interviews with five RMs will be used to argue that RMs are a key component in the co-innovation process and are required to play diverse roles depending on project circumstances to enhance system innovation – for example, devil's advocate, project supporter, consensus seeker, conflict mediator, critical enquirer or encourager. The findings have implications for the characteristics that make a good RM in terms of openness to new ideas, facilitation and critical thinking skills and how they report on the practice of monitoring a project reflexively utilizing monitoring and evaluation techniques.